(untitled) (Journal of Vishwa Adarsha College, 2025)
This study explores the reasons why many citizens in Itahari Sub-Metropolitan City, Nepal, do not use e-forms independently for government services. It applies the Unified Theory of Acceptance and Use of Technology (UTAUT) to examine the effects of Social Influence (SIN), Facilitating Conditions (FCO), Trust in E-Government (TRU), Effort Expectancy (EEX), and gender differences. Data were collected from 122 citizens using mailed questionnaires and analyzed using SPSS. Results show SIN as the most significant predictor of e-form usage of habits (β = 0.277, p = 0.090), with females reporting higher social influence (p = 0.030). The regression model explained only 7.8% of the variance (R² = 0.078), indicating the influence of additional factors such as digital literacy. Findings highlight the importance of awareness campaigns, enhanced ICT infrastructure, simplified e-form platforms, and digital literacy initiatives to reduce reliance on third-party services.